2006
DOI: 10.1111/j.1365-4632.2006.02951.x
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus in CD30+ anaplastic large cell lymphoma involving the skin and lymphomatoid papulosis in South Korea

Abstract: Background Epstein-Barr virus (EBV)-associated cutaneous lymphoproliferative disorders are prevalent in Asia, and less frequent in Western countries. Aim To elucidate the possible association of EBV with CD30 + anaplastic large cell lymphoma (ALCL) involving the skin and lymphomatoid papulosis (LyP) in South Korea. MethodsIn situ hybridization for EBV-encoded small RNA (EBER) and immunohistochemistry including viral latent membrane protein-1 (LMP-1) were performed on formalin-fixed, paraffin-embedded skin spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…ENKTCL was newly included in the WHO‐EORTC classification, but does not appear in the EORTC classification, for PCL. In previous reports, NKTCL was not found to be related to Epstein–Barr (EBV) virus 15 . The proportion of ENKTCL associated with EBV in the recent Korean study was higher than that in Western countries.…”
Section: Discussionmentioning
confidence: 70%
“…ENKTCL was newly included in the WHO‐EORTC classification, but does not appear in the EORTC classification, for PCL. In previous reports, NKTCL was not found to be related to Epstein–Barr (EBV) virus 15 . The proportion of ENKTCL associated with EBV in the recent Korean study was higher than that in Western countries.…”
Section: Discussionmentioning
confidence: 70%
“…Earlier reports drew discrepant conclusions in this regard (reviewed in Herling et al 59), but more recent contributions have concluded that both systemic and primary cutaneous types of ALCL arising in Western patients are not associated with the virus 59 60. A certain degree of geographical heterogeneity might, however, exist as rare EBV-positive cases of cutaneous ALCL in Korean patients were recently reported 61. Importantly, a series of 10 ALK-positive ALCL showing histological features reminiscent of nodular sclerosis Hodgkin lymphomas were found to be EBV-negative, confirming the reliability of EBV detection as a potentially helpful diagnostic tool to distinguish between ALCL and Hodgkin disease 62…”
Section: Controversiesmentioning
confidence: 87%
“…T-cell lymphoproliferative disorders that have been reported to be EBV associated include a subset of peripheral T-cell lymphomas [78,79], AILT [80,81], extranodal nasal type NK/T-cell lymphoma [82], enteropathy-type T-cell lymphoma [83,84], γδ T-cell lymphomas (hepatosplenic and nonhepatosplenic) [85,86], T-cell lymphoproliferative disorders after chronic EBV infection [87], EBV-associated cutaneous T-cell lymphoproliferative disorders (especially in Asia) [88], and aggressive NK-cell leukemia/lymphoma [89].…”
Section: Ebv and T/nk-cell Lymphoproliferative Disordersmentioning
confidence: 99%